Pelatihan Pembuatan Batik Ramah Lingkungan Dengan Pewarna Alami (Ecoprint) - Mariaty Mariaty; Misyanto Misyanto; Ise Afitah; Ardiyansyah Purnama (Cenderabakti: Jurnal Pengabdian Kepada Masyarakat, 2022)
This activity aims to increase public understanding of the importance of conserving the environment and forest resources, as well as to create alternative economic opportunities for the residents of Mungku Baru village. The method used is the socializationof observation and explore ecoprint. The results achieved in this service activity are the creation of public understanding about the importance of forest natural resources for the lives of the surrounding community and how to preserve them and improve batik-making skills using natural dyes.